Genotype-Associated Variations in Hematology, Serum Metabolites and Carcass Characteristics in Local, ISA Brown and Rose Chickens - Albayati, Husham Jaafar Musa (American Journal of Botany and Bioengineering, 2026)
The paper tested hematological indices, serum biochemical parameters, and carcass traits in three different chicken genotypes i.e. local chickens, ISA-Brown (layer-type), and Rose (broiler-type). The design was properly randomized, where 18 market-sourced birds were used, six per genotype. Hematological variables assayed were red and white blood cell counts, hemoglobin concentration, packed cell volume, and the erythrocyte indices were mean corpuscular volume and mean corpuscular hemoglobin. Serum measurements included glucose level, total protein and total cholesterol. The weights of carcass mass, specific cut-up areas and weights of edible organs were taken after slaughter. The statistical analysis showed that there were no significant differences in the three genotypes in terms of red blood cell count, white blood cell count, hemoglobin level, and packed cell volume. On the other hand, erythrocyte indices had significant differences: the mean corpuscular volume was higher in local chicken, and the mean corpuscular hemoglobin concentration was higher in the case of ISA-Brown and Rose chicken. There are also significant differences between serum parameters of glucose, total protein and cholesterol. The ISA-Brown chickens were found to have higher weights of the breast, thighs, and wings as compared to the local chickens, which had higher weights of the gizzard. It was found that there were strong positive relationships between the weights of the breast and thigh with the serum glucose and cholesterol levels. To conclude, it is possible to state that significant physiological, metabolic, and carcass-related differences were observed among the investigated genotypes. These differences seem to be attributed by a difference in metabolic status and previous management habits instead of pre-existing genetic differences. Therefore, the results highlight the importance of the type of chicken in the comprehension of hematological and biochemical features.